2013
DOI: 10.3389/fmicb.2012.00434
|View full text |Cite
|
Sign up to set email alerts
|

Lower Respiration in the Littoral Zone of a Subtropical Shallow Lake

Abstract: Macrophytes are important sources of dissolved organic carbon (DOC) to littoral zones of lakes, but this DOC is believed to be mostly refractory to bacteria, leading to the hypothesis that bacterial metabolism is different in littoral and pelagic zones of a large subtropical shallow lake. We tested this hypothesis by three approaches: (I) dissolved inorganic carbon (DIC) accumulation in littoral and pelagic water; (II) O2 consumption estimate for a cloud of points (n = 47) covering the entire lake; (III) measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…We are aware that lakes generally present differences between pelagic and littoral zones, and that shallow areas are more influenced by benthic processes than pelagic zones They et al, 2013). However, our aim here was the temporal variability specifically in the littoral zone, since no spatial variation of pCO 2 and pO 2 in nutrients and chlorophyll a was recorded in Peri Lake (Hennemann and Petrucio, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…We are aware that lakes generally present differences between pelagic and littoral zones, and that shallow areas are more influenced by benthic processes than pelagic zones They et al, 2013). However, our aim here was the temporal variability specifically in the littoral zone, since no spatial variation of pCO 2 and pO 2 in nutrients and chlorophyll a was recorded in Peri Lake (Hennemann and Petrucio, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…In a study during 48 h in a subtropical lake, Tonetta et al (2015a) have recorded that the daily CO 2 dynamics was highly variable and related to organic carbon availability and bacterioplankton, but no spatial variation was studied by the authors. In another shallow subtropical lake, however, They et al (2013) found spatial variability between pelagic and littoral areas, where lower respiration rates were recorded at littoral areas, related to the macrophytes presence. In this way, more studies in subtropical areas are needed to fill the gaps of this knowledge and to understand how both spatial and temporal variation are related to physical conditions in shallow subtropical lakes.…”
Section: Introductionmentioning
confidence: 86%
“…Several factors may have added the observed higher temporal variability in GPP and NEP at the littoral site, such as macrophytes presence (Obrador and Petrus, 2013;They et al, 2013); sediments heterogeneity (Lauster et al, 2006); wind speed creating spatial patchiness of nutrients and organisms (Van de Bogert et al, 2012), and rainfall (Marotta et al, 2010) introducing allochthonous organic matter. Our methodology, however, did not allow us to access the direct importance of these variables for the observed temporal variability observed.…”
Section: Temporal Variabilitymentioning
confidence: 97%
See 1 more Smart Citation
“…We used multiple linear regression, artificial neural network, nonparametric multiplicative regression, and four models (Appel, Kahru,FAI and O14a) to retrieve the Chl-a concentration in the Lake Mangueira, a large shallow subtropical lake located in Southern Brazil. This approach is the first attempt to assess the application of remote sensing techniques in such a system, which the oligotrophic conditions are common most of the time (CROSSETTI et al, 2013;LIMA et al, 2016), and the spatial heterogeneity has large differences between the littoral and pelagic zones (CARDOSO et al, 2012;CROSSETTI et al, 2013;THEY;SOUZA, 2012).…”
Section: Introductionmentioning
confidence: 99%